Analisis Putusan Hakim Tentang Delik Perbankan Terkait Pengembalian Dana Debitur Dalam Rangka Penyelesaian Kredit Bermasalah (Studi Kasus Putusan Mahkamah Agung Nomor 7716 K/Pid.Sus/2022/Ma) - Riauroikha, Hilmalia Sesy; Nuraini, Lia (UNES Law Review, 2023)
Banking plays a vital rolein a country's economy as an institution that collects funds from the public and distributes them through credit to support development.the public and distributes them through credit to support national development.development. However, the problem of non-performing loans often gets in the way,forcing banks to to find solutions including through the submission of repossessed collateral (AYDA).The resolution of non-performing loans involves credit evaluation, notification to the borrower, collateral valuation, collateral valuation, and collateral repossession. notice to the borrower, collateral valuation, agreement with the borrower, execution of collateral, auction or sale of collateral. execution, auction or sale of collateral, credit repayment, and reconciliation. This research reviews a case of banking crime involving the return of funds from the sale of collateralized assets. In this context, the court ruled that the action was not unlawful, but the Supreme Court overturned this ruling on the grounds that the verdict on the grounds of violation of Standard Operating Procedure (S.O.P), even though the refund was actually approved by the Board of Commissioners. the return had actually been approved by the Board of Commissioners. An analysis of analysis showed that the court's decision was more prudent and in accordance with the applicable laws and regulations. However, the Supreme Court gave a controversial. However, the Supreme Court gave a controversial decision by declaring the action as a criminal offense, even though fraud was absent and all processes had been properly followed. The results of this research provide a better understanding of the complexities of the and the role of the courts in assessing the actions of banks. actions of the bank. This research highlights the need for clarity in banking laws and protection of bank actions that are in accordance with the procedures regulated by law and the competent authority.